THE INFLUENCE OF THIRD-PARTY FUNDS, NON-PERFORMING LOANS (NPL) ON CREDIT DISTRIBUTION WITH PROFITABILITY AS INTERVENING VARIABLE IN COMMERCIAL BANKS - Hermuningsih, Sri; Sari, Pristin Prima; Rahmawati, Anisya Dewi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Banks are financial institutions that collect and distribute funds in the forms of deposits such as savings, deposits, current accounts, etc. from and for people who need funds for various needs, such as for consumption, working capital or business capital, housing and investment. In addition, banks must help the community to improve their living standards by distributing funds or giving credit to people who need funds. This is in accordance with the function of the bank itself, namely the bank as the distributor of funds. The purpose of this research is to examine and obtain evidence about factors that influence loan distribution at a bank. Internal factors that influence loan distribution are Third Party Funds, Non-Performing Loans, and Profitability. Efforts to increase credit at banks require optimal efforts to raise third-party funds, good credit management, and capital strengthening. This type of research is quantitative research with purposive sampling technique. The population used in this study is commercial banks from 2013 to 2017. The data come from commercial bank financial statements. As the benefit of this research the government can use it as a mapping material for distributing loan to commercial banks; the bank management can take it into consideration in making commercial bank lending policies. The results of the research show that profitability can mediate the relationship between third party funds and non-performing loans on loan distribution. Third party funds have a significant positive effect on loan distribution. Non-Performing Loans have a significant negative effect on loan distribution. Keywords: LOAN DISTRIBUTION, THIRD PARTY FUNDS, NON-PERFORMING LOANS, AND PROFITABILITY